E-learning in higher education institutions after the Corona pandemic:: Reality and Challenges - Ramdani, Hamza (Journal of Human Sciences, 2022)
The traditional education at the present time did not add new to the educational content of the generations because it alone cannot keep pace with modern thought, and the Arab world needs a shift in quantity and quality for the students of the twenty-first century, as the level of education is very low compared to international countries. E-learning has enjoyed a great expansion in the Corona pandemic as an alternative to traditional education, as e-learning is spreading rapidly in higher education institutions all over the world, and has even taken up a large part of the income of some universities. After the Corona pandemic in higher education institutions, giving recommendations and suggestions for the optimal exploitation of e-learning.